Novel Microstrip Ultra-Wideband Bandpass Filter Using Radial-Stub-Loaded Structure - Xida Deng; Kai Da Xu; Zhigang Wang; Bo Yan, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A novel planar ultra-wideband (UWB) bandpass filter (BPF) using radial-stub-loaded resonator is proposed, where the resonator consists of three radial stubs, one located in the middle and two symmetrically at both sides. This radial-stub-loaded structure situates the first four resonant modes in the UWB passband (3.1~10.6 GHz) and makes the fifth resonant mode far away from this passband. To enhance the coupling degree, two interdigital coupled feed lines are utilized in this UWB filter. Finally, a UWB BPF with wide upper-stopband and sharp upper rejection skirt has been realized and its design steps have been also presented. The measured and full-wave simulated results of the proposed filter are in good agreement.